The Importance of Leadership and Organizational Culture for Social Sustainability - Hillman Mushaddiq Suaidy; Adler Haymans Manurung (Dinasti Publisher, 2023)
Challenge in build continuity mainly in realize social sustainability is a thing to be challenge for every element in good individual or group. With the exists study of this, the aims is to review the exists of the resulting influence leadership and culture organization in build social sustainability in a organization. The method approach takes targets the study of supporting literature that has the same vision as this research. The results of the review show that both leadership and organizational culture have an important role in building social sustainability. This shows that the collaboration of the two conditions can maximize the potential for social sustainability that will be built in the future.